Case Report: Effects of Anti-SARS-CoV-2 Convalescent Antibodies Obtained With Double Filtration Plasmapheresis - Curtò, Diego; Tomatis, Federica; Gastoldi, Sara; Galbusera, Miriam; Noris, Marina; Raimondi, Federico; Lorini, Ferdinando Luca; Falanga, Anna; Marchetti, Marina; Remuzzi, Giuseppe; Ruggenenti, Piero (Frontiers in Immunology, 2021)
Passive antibody therapy has been used to treat outbreaks of viral disease, including the ongoing pandemic of Severe Respiratory Acute Respiratory Syndrome (SARS) Coronavirus 2 (SARS-CoV-2) or COVID-19. However, the real benefits of the procedure are unclear. We infused a concentrated solution of neutralizing anti-SARS-CoV-2 antibodies obtained from a convalescent donor with a single session of double filtration plasmapheresis (DFPP) into a 56-year-old woman with long history of unremitting, severe COVID-19. She was unable to establish an adequate antiviral immune response because of previous chemotherapy, including the infusion of the anti-CD20 monoclonal antibody rituximab, administered to treat a diffuse large B-cell lymphoma. The disease promptly recovered despite evidence of no endogenous anti-SARS-CoV-2 antibody production. The observation that passive antibody therapy might prove particularly effective in immunodepressed COVID-19 patients requires evaluation in prospective randomized controlled trial.